Wnt signaling pathway in spinal cord injury: from mechanisms to potential applications - Li, Kai; Chen, Zanzhi; Chang, Xuejing; Xue, Ruiyang; Wang, Huaibo; Guo, Weitao (Frontiers in Molecular Neuroscience, 2024)
Spinal cord injury (SCI) denotes damage to both the structure and function of the spinal cord, primarily manifesting as sensory and motor deficits caused by disruptions in neural transmission pathways, potentially culminating in irreversible paralysis. Its pathophysiological processes are complex, with numerous molecules and signaling pathways intricately involved. Notably, the pronounced upregulation of the Wnt signaling pathway post-SCI holds promise for neural regeneration and repair. Activation of the Wnt pathway plays a crucial role in neuronal differentiation, axonal regeneration, local neuroinflammatory responses, and cell apoptosis, highlighting its potential as a therapeutic target for treating SCI. However, excessive activation of the Wnt pathway can also lead to negative effects, highlighting the need for further investigation into its applicability and significance in SCI. This paper provides an overview of the latest research advancements in the Wnt signaling pathway in SCI, summarizing the recent progress in treatment strategies associated with the Wnt pathway and analyzing their advantages and disadvantages. Additionally, we offer insights into the clinical application of the Wnt signaling pathway in SCI, along with prospective avenues for future research direction.